Midwives and Herbal Remedies: The Sustainable Ethnoscience - Kartini Aboo Talib @ Khalid; Mohamed, Nurshuhada (Kajian Malaysia, 2020)
The traditional Malay practices of pre and postnatal care have been fascinating to help understand women’s health and reproductive role. Women within midwives and midwifery contexts made their status recognised back in the ancient practice. The ethnoscience methods about women’s health have been the centre of discussion way back in the Aztec, Mayan and Egyptian civilisations, yet the topic never gets exhausted. The ethnographic research on midwives conducted in Terengganu in the 1980s and other new literature provided a variation to the study of midwives. This article attempts to revisit the observation of midwives on herbal remedies and other healing processes after a gap of more than 30 years. The question remains whether or not this traditional practice, including herbal intake for diet, bath and massage is sustained in this millennium society. Also, this article analyses the factors and reasons for the persistence of such methods. This research utilises participant observation and intensive interviews with midwives from the west coast of Malaysia. A similar pattern of answers provides essential themes on the utilisation of ethnoscience knowledge on women and health, especially the benefits of herbal remedies for fertility, pregnancy, pre, and postnatal care. Furthermore, practice and belief integrate into modern medicine. The expression of such methods manifests in the cultural capital that views the healing process is integral. As a result, this ethnoscience phenomenon reinvents in a new commercial form that fits modern medicine as a way to rejuvenate women after childbirth.